Catechol- and phenolic hydroxyl-functionalized partially bio-based (Co) poly(ether sulfone)s with multifarious applicability - Wale, Apparav K.; Jagtap, Ashish S.; Pandey, Priyanshi R.; Dastager, Syed G.; Shelke, Manjusha V.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2024)
A largely bio-based new bisphenol, namely, 4,4 `-((3,4-dimethoxyphenyl)methylene)-bis(2-methoxyphenol) (DMBM) was synthesized by the reaction of veratraldehyde with guaiacol. DMBM and varying compositions of DMBM and bisphenol A were polycondensed with bis(4-fluorophenyl) sulfone to afford reasonably high molecular weight film-forming (co)poly(ether sulfone)s possessing built-in methoxyl groups. T10 and Tg values of (co)poly(ether sulfone)s were in the range 382-478 degrees C and 171-187 degrees C, respectively indicating their good thermal stability and the values decreased with increase in mol % incorporation of DMBM. The methoxyl groups present in (co)poly (ether sulfone)s were quantitatively de-blocked resulting in the formation of corresponding polymers possessing pendant catechol moieties and free phenolic hydroxyl groups. By virtue of the presence of these functional moieties, (co)poly(ether sulfone)s are amenable for post-polymerization modifications, and exhibited properties such as antimicrobial (23 mm against Staphylococcus aureus and 18 mm against Escherichia coli)), antioxidant (72 % scavenger of free radicals), adhesive (2.24 MPa lap shear strength) and usefulness as redox-active agent in zinc-ion batteries. These data underscore the promise of DMBM as a versatile monomer of wider utility for the synthesis of functional (co)poly(ether sulfone)s capable of expanding their applicability beyond the conventional ones.
Keywords: (Co)poly(ether sulfone)s; adhesive; Antimicrobial; Antioxidant; bio-based; bisphenol; Zinc-ion batteries

Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation

Study of disulfide-based di-epoxy resin as an anti-corrosive paint with modification by graphene and carbon nanotube - Patel, Jay K.; Joshi, Medha; Desai, Dhaval; Wale, Apparav K. (Journal of the Indian Chemical Society, 2026)
In this study, we synthesized a disulfide-based epoxy resin using dithiodibenzoic acid in combination with epichlorohydrin and a caustic additive. The identification of the epoxide group was confirmed by IR, NMR, and Epoxy equivalent weight. The thermal stability was investigated using a thermogravimetry curve. Surface morphology of paint samples was investigated by SEM. Paint was prepared with the addition of zinc powder, zinc phosphate, calcium carbonate, along with fillers, additives, and solvents like butanone and xylene, an aromatic polyamine adduct hardener. The paint was modified by the addition of 1.0 wt% graphene and 0.05 wt% carbon nanotube (CNTs), and compared its anticorrosion application against an unmodified paint sample. The result suggested that the addition of graphene and CNTs enhanced the mechanical strength of the paint and also improved the chemical resistance against corrosion.
Keywords: Anticorrosive properties; CNTs; Coating; Epoxy resin; graphene; Mechanical characteristics

Utilization of bisphenol based on lignin-derived chemicals for the synthesis of partially bio-based aromatic copolyesters - Wale, Apparav K.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
New aromatic copolyesters were synthesized by phase-transfer catalyzed interfacial polycondensation of 4,4 `-((3,4-dimethoxyphenyl)methylene)bis(2-methoxyphenol) (DMBM) with isophthaloyl chloride (IPC) and a mixture of (50:50 mol %) IPC and terephthaloyl chloride (TPC). Additionally, a series of copolyesters was synthesized by polycondensation of varying compositions of DMBM and bisphenol A with IPC. Copolyesters exhibited inherent viscosity and Mn values in the range 0.59-0.98 dL/g and 15,840-49,460 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Copolyesters could be cast into tough, transparent and flexible films from chloroform solution. UV-vis measurements on films gave values of T400, T450 and cut-off wavelength in the range 80-84 %, 83-89 % and 324-334 nm, respectively. The formation of random copolyesters was evidenced by 13C NMR spectroscopic studies. Copolyesters exhibited good thermal stability with 10% weight loss temperature in the range 391-438 degrees C. The Tg values of copolyesters were in the range 162-180 degrees C and Tg values decreased with an increase in mol% content of DMBM. Copolyesters exhibited tensile strength, Young's modulus and elongation at break values in the range 83.55-70.68 MPa, 2.11-1.31 GPa and 10.52-5.45 %, respectively.
Keywords: Aromatic polyesters; bio-based; bisphenol; methoxyl; Thermal properties